(A Critical Appraisal of) Classification of Hypereosinophilic Disorders - Kahn, Jean Emmanuel; Groh, Matthieu; Lefèvre, Guillaume (Frontiers in Medicine, 2017)
Hypereosinophilia (HE) is a heterogeneous condition that can be reported in various (namely inflammatory, allergic, infectious or neoplastic) diseases with distinct pathophysiological pathways. In 1975, Chusid et al. published the first diagnostic criteria of HE syndromes (HES). Over the years, as both basic and clinical knowledge improved, several updates have been suggested, with a focus on better distinguishing isolated or asymptomatic eosinophilia from diseases with specific eosinophil-related organ damage. Moreover, underlying molecular and cellular mechanisms of eosinophilia gradually became the cornerstone of successive attempts to classify HE-related diseases. In 2011, the ICOG-EO criteria emerged from a multidisciplinary Working Conference on Eosinophil Disorders and Syndromes, and provided substantial contribution to the clarification of general concepts and definitions in the field of HE. Yet, owing to the low prevalence of HE/HES, to the numerous diseases encompassed in the spectrum of HE-related disorders (with sometimes overlapping phenotypes), many questions are left unanswered (e.g. the need to better standardize the use of modern molecular tools, or the clinical relevance of distinguishing different subtypes of idiopathic HES). Here, we review the current state of knowledge in the fields of classification and diagnosis criteria of HE-related diseases, with emphasis on the analysis of both strengths and weaknesses of present concepts and their usefulness in daily practice.